2021
DOI: 10.1055/a-1545-7563
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Transfer Hydrogenation for Construction of Quinolines from 2-Aminobenzyl Alcohols with Enones in Water

Abstract: Herein, we describe a method for the synthesis of functionalized quinolines from 2-aminobenzyl alcohols with α, β-unsaturated ketones. This method exhibits various functional groups tolerance, high-efficiency, environmentally benign and can be performed on a gram scale. Control experiment suggests this transformation is accomplished by iridium complex-catalyzed transfer hydrogenation, which is then followed by the Friedländer cyclization. The results display the alkali is essential for the high selectivities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Aromatic secondary alcohols substituted with electron-donating groups led to higher chemoselectivities and yields of the products (Table 3, entries 2-5) than the aryl secondary alcohols and aminobenzyl alcohol with electron-withdrawing groups (Table 3, entries 8, 11, 12, 15, 16, 19, 20, 23, and 24). Meanwhile, the heteroaromatic secondary alcohols 2i-n could also be employed in the cyclometalated iridium-catalyzed system obtaining the products 3ai-an with excellent yield and chemoselectivity (Table 3, entries [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The results showed that the yield and chemoselectivity was higher when the heteroaromatic secondary alcohols and aminobenzyl alcohols have electron-donating groups (Table 3, entries 27, 30, 31, 34, 35, 39, and 42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aromatic secondary alcohols substituted with electron-donating groups led to higher chemoselectivities and yields of the products (Table 3, entries 2-5) than the aryl secondary alcohols and aminobenzyl alcohol with electron-withdrawing groups (Table 3, entries 8, 11, 12, 15, 16, 19, 20, 23, and 24). Meanwhile, the heteroaromatic secondary alcohols 2i-n could also be employed in the cyclometalated iridium-catalyzed system obtaining the products 3ai-an with excellent yield and chemoselectivity (Table 3, entries [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The results showed that the yield and chemoselectivity was higher when the heteroaromatic secondary alcohols and aminobenzyl alcohols have electron-donating groups (Table 3, entries 27, 30, 31, 34, 35, 39, and 42).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies [39][40][41][42], we found that cyclometalated iridium catalysts can effectively catalyze the dehydrogenation of alcohols to produce carbonyl compounds and hydrogen gas. Therefore, we used cyclometalated iridium complex (TC-6) to catalyze the ADC reaction of o-aminobenzyl alcohols 1 and aryl/heteroaryl/alkyl secondary alcohols 2 that allowed for the efficient synthesis of a series of quinolines 3 (up to 95% yield and >99:1 selectivity) (Figure 2).…”
Section: Introductionmentioning
confidence: 95%
“…Another synthesis of quinolines via the reaction of 2-aminobenzyl alcohols with enones was reported by Luo et al in the same year. [42] The reaction was carried out in the presence of 0.1 mol% of an iridium catalyst and 1.0 equivalent of tBuOK in toluene, and two products of quinoline and tetrahydroquinoline were obtained with a relatively ratio of 99:1 in most cases.…”
Section: Metal-catalyzed Synthesis Of Quinolinesmentioning
confidence: 99%
“…On the basis of the widely used synthesis of commercially available chalcones, 13 we have developed an efficient method for the synthesis of polysubstituted NH-pyrroles directly from α,β-unsaturated sulfonimines, which have been shown by Loh, 14 Smith, 15 and Yoshikai 16 to be good precursors for the construction of multisubstituted pyridines (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%